Impact of Toll-like-receptor-9 (TLR9) Deficiency on Visceral Adipose Tissue Adipokine Expression during Chronic DSS-induced Colitis in Mice - Karrasch, T.; Schmid, A.; Kopp, A.; Obermeier, F.; Hofmann, C.; Schäffler, A. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Background: Studies postulate an involvement of adipokines in inflammatory gastrointestinal diseases. Leptin-deficient ob/ob mice as well as TLR9-deficient mice have a more moderate course of chronic DSS-induced colitis (DSS-CC) and adipocytes do express functional TLR9 molecules.Material and Methods: Adipokine mRNA expression in visceral adipose tissue of mice before and after the induction of DSS-CC was investigated. Experiments were performed in both TLR9wt/wt and TLR9-/- mice. In vitro, the effect of TLR9 blocking peptide on leptin and visfatin protein secretion was studied in 3T3-L1 adipocytes.Results: Induction of DSS-CC led to an upregulation of leptin mRNA expression in TLR9wt/wt mice, while TLR9-/- animals showed a significant reduction of leptin expression even below baseline. While visfatin expression remained unchanged in TLR9wt/wt animals, TLR9-/- mice exhibited a significant induction during DSS-CC. CTRP-3 expression was reduced after colitis induction only in TLR9-/- animals. Of note, IL-6 expression levels remained unchanged, while CXCL1/KC and cyclophilin A expression was reduced in DSS-CC. Inhibition of TLR9 signaling by using TLR9 blocking peptide led to reduced leptin protein secretion into cell culture supernatants in 3T3-L1 adipocytes, while visfatin protein secretion was enhanced.Conclusions: DSS-CC leads to differential adipokine expression profiles in the visceral fat pad in TLR9wt/wt vs. TLR9-/- mice. In vitro, inhibition of TLR9 signaling induces visfatin secretion while inhibiting leptin secretion in adipocytes. Thus, visceral adipokines are regulated by intact TLR9 signaling pathway and a specific interplay between the leptin- and the TLR9-pathways might be of pathophysiological importance in chronic intestinal inflammation.
Keywords: leptin; visfatin; CTRP-3; IL-6; visceral adipose tissue; TLR9; DSS; chronic colitis